Efficient synthesis of diverse hetero-bis-metallated alkenes as modular reagents towards highly conjugated and isolated olefinic systems - Altendorfer, Mario; Menche, Dirk (Chemical communications, 2012)
An efficient synthesis of diverse hetero-bis-metallated alkenes with conjugated and isolated olefin subunits is reported. Relying on those useful tin/boron reagents a convergent, palladium-catalyzed fragment coupling strategy has been developed as an elegant methodology to construct highly conjugated polyenes and stabilized olefinic analogues thereof. The utility of these reagents was further demonstrated in a concise and modular construction of extended polyene side chains of the potent polyketide antibiotic etnangien.